ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEREKONOMIAN DAN PENERIMAAN PAJAK DI INDONESIA - Handoko, Iwan; Aimon, hasdi; Syofyan, Efrizal (Jurnal Kajian Ekonomi, 2014)
This study aims to analyze and determine (1) the effect of the tax revenue, money supply, employment, consumption, investment, government spending, and net exports to Indonesia's economy, (2) the effect of the economy, poverty level, the policy of taxing (Act No.36 of 2008) to tax revenues in Indonesia. This research is descriptive and associative. While this type of data is the documentary data and the data source is a secondary data in the form of time series from 1970-2012. Research use simultaneous equation model analysis of Two Stage Least Squared method (TLS). The result of study that (1) Variable of tax revenue, money supply, employment, consumption, investment, government spending, and net exports influential positive and significant towards the economy in Indonesia. (2) the economic variables, poverty level, and policy of taxing influential positive and significant towards tax revenues. Based on these results the policies that can be recommended is that the government needs to increase the real sector productivity (output) through incentives such as tax reduction, given the ease of investment regulations, and improve the quality and quantity of export product diversification. Determination of the amount of tax revenue target should pay more attention to macroeconomic indicators, while the increase in institutional functioning of the Directorate General of Taxes, Ministry of Finance in order to focus on the implementation and improvement of tax administration measures. Keywords: Economy, tax revenues, government spending, income per capita, the policy of taxing